PENGARUH PENERAPAN STRATEGI LEARNING STARTS WITH A QUESTION TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS IX SMPN 2 RANAH BATAHAN KABUPATEN PASAMAN BARAT - Yanti, Ida; K, Delsi (STKIP PGRI Sumbar, 2013)
This research based of the studentsâ mathematical concept comprehension is low and they do not dare to ask one question to their teacher.Â The purpose of this research is to know whether the studentsâ mathematical concept comprehension by applying the strategy of Learning Starts With A Question is better than that using the conventional learning at the grade-IX class of SMPN 2 Ranah Batahan Kabupaten Pasaman Barat. The type of research is an experiment with design random on the subject. The testing of hypothesis is made using one side t test with an assistance of MINITAB software; it is obtained that P-value is 0,036 being smaller than Î± of 0,05. Thus, the proposed hypothesis is accepted. It can be concluded that the studentsâ mathematical concept comprehension by applying the Learning Starts with A Question strategy is better than that using the conventional learning at the grade-IX class of SMPN 2 Ranah Batahan Kabupaten Pasaman Barat.